Demographical Distribution on the Incidence of Helicobacter pylori Infection in Jakarta: Obtaining Samples from 5 Municipalities - Ari Fahrial Syam; Achmad Fauzi; Murdani Abdullah; Marcellus Simadibrata; Dadang Makmun; Chudahman Manan; Abdul Aziz Rani (The Indonesian Society for Digestive Endoscopy, 2014)
Background: Currently, the hospital-based studies on Helicobacter pylori (H. pylori) have demonstrated that the incidence of H. pylori infection tends to decline in Indonesia. On the other hand, no population-based study has ever been conducted. Therefore, our study was performed to evaluate the true incidence of H. pylori found among the population.Method: This study was a surveillance using cross-sectional design. The samples used in our study were randomly selected from 1,645 samples including those from five municapalities of Special Capital Region of Jakarta in 2006. Immunochromatographic test (ICT) was utilized to establish the diagnosis of H. pylori infection. The test has demonstrated high sensitivity and specificity for Indonesian populationResults: The seroprevalence of H. pylori infection among 310 patients was 52.3% (162 out of 310 patients) with mean age of 43.48 + 10.45 years. There was no difference regarding seroprevalence in both groups of 40 year and 40 years of age (52.3% and 52.2%). The highest prevalence of H. pylori infection was found in West Jakarta (66.1%); while the lowest prevalence was found in South Jakarta (41.0%). The incidence of H.pylori infection between those who were alcoholic was equal to those who were not alcoholic (46.2% vs. 52.5%).Similar result was also found between smokers and non-smokers (53.8% vs. 51.8%).Conclusion: In this study, we found that H. pylori seroprevalence remains high in the population. Various seroprevalence of H.pylori infection were found among five municipalities in Jakarta.Keywords: Helicobacter pylori, Jakarta, seroprevalence